Application of compositional fingerprinting to an italian site contaminated by hydrocarbons - Trefiletti, Patrizia; Pietrini, Ilaria; Rigamonti, Dario; Alberti, Luca (Italian journal of engineering geology and environment, 2014)
In this paper, a case study of compositional fingerprinting application to characterize an italian site, with evidence of hydrocarbons contamination, is presented. Though the fingerprinting approach is not widely used, especially in italy, this methodology permits to identify the type of contamination and its level of degradation by the study of the homologues classes of contaminants present in the mixtures. In characterization of contamination due to spillage of diesel, through the use of specific ratios between compounds of the mixture, it is possible to determine the contaminant grade of alteration and thus gives a prediction of the contamination age. In case study here presented, using the ratio heptadecane/pristane (n-C17/ pr), a prediction of the contamination age was carried out for the identified diesel contamination. These aspects are also fundamental for a correct characterization of the site and therefore to choose the most suitable site-specific remediation strategy. All these data, combined with the usual geochemical analysis, can give an added value in order to assess the responsibility of contamination and therefore the duty of reclamation, especially in case of different owners. in this way, a successful reclamation, from the point of view of both the expected results and the economic view, is possible.